Intraoperative Hypertension and Thrombocytopenia Associated With Intracranial Hemorrhage After Liver Transplantation. Issue 3 (March 2020) - Gao, Wei; Li, Jun; Nguyen-Buckley, Christine; Nguyen-Lee, Jennifer; Wray, Christopher; Agopian, Vatche; Busuttil, Ronald W.; Steadman, Randolph H.; Xia, Victor W.
Abstract : Background: Intracranial hemorrhage (ICH) is a devastating complication. Although hypertension and thrombocytopenia are well-known risk factors for ICH in the general population, their roles in ICH after liver transplantation (LT) have not been well established. Methods: We performed a retrospective study and hypothesized that intraoperative hypertension and thrombocytopenia were associated with posttransplant ICH. New onset of spontaneous hemorrhage in the central nervous system within 30 days after LT were identified by reviewing radiologic reports and medical records. Risk factors were identified by multivariate logistic regression. Receiver operating characteristic analysis and Youden index were used to find the cutoff value with optimal sensitivity and specificity. Results: Of 1836 adult patients undergoing LT at University of California, Los Angeles, 36 (2.0%) developed ICH within 30 days after LT. Multivariate logistic regression demonstrated that intraoperative mean arterial pressure ≥105 mm Hg (≥10 min) (odds ratio, 6.5; 95% confidence interval, 2.7-7.7; P < 0.001) and platelet counts ⩽30 × 10 9 /L (odds ratio, 3.3; 95% confidence interval, 14-7.7; P = 0.006) were associated with increased risk of postoperative ICH. Preoperative total bilirubin ≥7 mg/dL was also a risk factor. Thirty-day mortality in ICH patients was 48.3%, significantly higher compared with the non-ICH group (3.0%; P < 0.001). Patients with all 3 risk factors had a 16% chance of developing ICH. Conclusions: In the current study, postoperative ICH was uncommon but associated with high mortality. Prolonged intraoperative hypertension and severe thrombocytopenia were associated with postoperative ICH. More studies are warranted to confirm our findings and develop a strategy to prevent this devastating posttransplant complication.